Teori konflik sosial Dean G. Pruit, Jeffrey Z.Rubin; penerjemah, Helly P. Soetjipto, Sri Mulyani Soetjipto; penyunting, Muhammad Khatamie - PRUIT, Dean G; Khatarine, Muhammad; Sucipto, Sri Mulyantini; Sucipto, Helly P; Rubin, Jefrey (2004)
xiv, 456 hlm ilus 21 cm